Managerial extraversion and corporate voluntary disclosure - Eugster, Florian; Kallunki, Jenni; Kallunki, Juha‐Pekka; Nilsson, Henrik (Contemporary Accounting Research, 2024)
Abstract This article examines the effect of managers' personality trait of extraversion on the voluntary disclosure of their firms. Our results from analyzing archival data from Sweden show that the extraversion scores of CEOs and CFOs obtained from psychological tests are positively associated with the voluntary disclosure scores of their firms. The effect of managerial extraversion on disclosure is, moreover, stronger when managerial discretion or managerial job demands are higher. We also find that extraversion affects managers' disclosure styles during earnings conference calls.